OVERVIEW OF NATIONAL AND GLOBAL SCENARIO OF CONSTRUCTION INDUSTRIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
By 2025, the contribution of construction industry in India’s GDP is expected to be more than 10%. Better infrastructure is a sign of development of any country. Construction industries in the developed countries are not only working on infrastructure development but also to produce the international quality infrastructure. The GDP of the country is always supported to great extent by the construction industries. For the developing countries like India the scope for betterment of infrastructure is still a challenge to take. The current Indian government is focusing on the infrastructure development and improvement in technology. In this paper, author has tried presenting the national and global scenario of construction industries. Infrastructure development always plays a vital role in the economic development of the country. The infrastructure development is mainly carried out by construction industries. The challenge of today’s construction industries is to utilize the technology in order to upgrade the quality of construction projects. Moreover, the construction industries contribute directly and indirectly as well for the development of country.